Development of Clinical Nursing Practice Guideline for Prevention Unplanned Extubation - Thongjam, Rattana (Journal of Vongchavalitkul university, 2020)
Objective: This research and development study was aiming to develop and study the outcomes of the clinical nursing practice guideline for prevention unplanned extubation. Methods: The study consisted of 4 phases, phase 1 was exploring situation, reviewing existing nursing practices guidelines and observing the current practice. Phase 2 was developing a clinical nursing practice guideline for prevention of unplanned extubation, Phase 3 was implementing the nursing practice guideline. Samples in this phase were 20 professional nurses and 78 patients requiring mechanical ventilators. The patients were divided into control and experimental groups, 39 each. Phase 4 was evaluating the results. Data were collected and analyzed using descriptive statistics, frequency and percentage and comparison of differences between the control group and the experimental group using Chi-Square. Results: Results of the clinical nursing practice guideline development displayed in four phases. Phase 1: exploring the situation, it was found that the nursing practice guidelines for prevention of unplanned extubation did not cover all the factors that cause unplanned extubation and nursing practice guidelines for prevention of unplanned extubation of the department was not well organized. Phase 2: developing a clinical nursing practice guideline for prevention of unplanned extubation was conducted by reviewing previous evidence best practice guidelines. After content validity and feasibility assessment were done, the developed clinical nursing practice guidelines for prevention of unplanned extubation consisted of 7 sub-guidelines: 1) risk assessment of unplanned extubation guideline, 2) education for intubation patient guideline, 3) communication guideline, 4) suction guideline, 5) endotracheal tube stabilization guideline, 6) weaning guideline, and 7) body restraint guideline. Phase 3: implementation of the nursing practice guidelines was conducted by establishing a conference to clarify the guidelines, practicing of related procedures, and performing in daily clinical nursing practice. Phase 4: the results after implementation clinical nursing practice guideline revealed that the experimental groups had significantly lower incident of unplanned extubation than the control group (p < .05)